A method for controlling impurities in sapphire crystal growth and a crucible for crystal growth
By spraying the aluminum oxide solution on the inner wall of the molybdenum crucible for the growth of sapphire crystals, the aluminum molybdate protective layer is formed, and the problem of free molybdenum elements is solved in the sapphire crystals, improving the quality of the crystals and the service life of the crucible.
Patent Information
- Application Number
- CN202411092274.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-09
AI Technical Summary
During the growth of sapphire crystals, it is difficult to completely remove free molybdenum elements in the new molybdenum crucible, resulting in high content of impurities in the crystals, affecting crystal quality and stability.
By spraying the inner wall of the molybdenum crucible with aluminum oxide solution, a protective layer of aluminum molybdate is formed to prevent the chemical reaction between the molybdenum element and the alumina raw material, thereby controlling the molybdenum element content in the crucible.
It effectively reduces the generation of grain boundaries, stress and bubbles in the crystal, avoids crystal discoloration, improves the quality and stability of sapphire crystal growth, and extends the service life of the crucible.
Smart Images

Figure CN118621429B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sapphire crystal growth, and in particular relates to a sapphire crystal growth impurity control method and a crucible for crystal growth. Background Art
[0002] In the crystal growth process, the crucible is a crucial component. Since the molybdenum crucible has good thermal conductivity and low thermal expansion coefficient, it is a commonly used crucible for growing high-melting-point crystals. At present, sapphire crystals are mainly grown using the Kyropoulos method, also known as the KY method. Since the crucible is usually made of metal molybdenum and its alloy powders through isostatic pressing, processing and sintering, there are free impurity elements in the crucible during this process. Therefore, when a new molybdenum crucible is put into the crystal growth process for the first time, impurity elements may be introduced into the crystal, especially free molybdenum elements. These elements have a direct impact on the quality of the crystal during the growth of sapphire crystals.
[0003] At present, in the industrial production process of sapphire crystals, the quality improvement of sapphire crystal growth is mainly to control impurities during the crystal growth process. In essence, it is to control impurities in new molybdenum crucibles. The method mainly includes two steps: first, before using the new crucible, fill the crucible with pure water and then perform ultrasonic cleaning; second, put the crucible into the crystal growth furnace and heat it empty for 1 time or more, and keep the temperature at about 2050℃ for at least 24 hours. However, this method still cannot completely remove the free molybdenum element produced by the crucible forming process that is not tightly pressed. It will be mixed into the first few batches of crystal raw materials grown in the new crucible. During the crystal growth process, aluminum atoms will enter the vacancies or gaps, and the lattice will be distorted to varying degrees. Molybdenum impurities at the macro level will cause the crystal to discolor, affecting the crystal quality and not conducive to application.
[0004] Patents with publication numbers CN108727023A and CN110818413A disclose that aluminum oxide and molybdenum trioxide will undergo a solid phase reaction at high temperatures to generate aluminum molybdate. It can be seen that free molybdenum elements will react with aluminum oxide crystal growth raw materials at high temperatures, resulting in the generation of grain boundaries and stresses during the sapphire crystal growth process, as well as the appearance of bubbles inside the grown sapphire crystals. In addition, excessive molybdenum elements and other impurity elements may also cause the crystals to appear light green or other colors. In order to solve similar problems mentioned above, a patent with publication number CN220116725U discloses a crucible for a graphite hot field crystal growth furnace. An inner lining layer and a transition layer are provided inside the molybdenum crucible to prevent the crystal growth raw materials from adhering to molybdenum and affecting the crystal quality. This is a physical isolation method and does not involve spraying an aluminum oxide raw material coating on the inner wall of the crucible to control the chemical reaction between aluminum oxide and molybdenum elements. The patent with announcement number CN103361722B provides a method for preparing polycrystalline silicon ingots. High-quality polycrystalline silicon ingots are prepared by spraying a barrier coating on the inner wall of a crucible that has been sprayed with a silicon nitride coating. This method aims to solve the problem of reaction between silicon material and the original silicon nitride coating on the inner wall of the crucible. A barrier layer is added on the premise of an existing coating to avoid chemical reactions through barrier means. In essence, it is a physical isolation method.
[0005] Therefore, during the growth of sapphire crystals, the content of molybdenum must be strictly controlled to ensure the quality and stability of the crystals. In view of this problem, a method for controlling impurities in the growth of sapphire crystals is now needed. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for controlling impurities in sapphire crystal growth. The method mainly utilizes the reaction design and control of aluminum oxide at different temperatures, and through the crucible impurity removal operation, avoids the introduction of impurity elements in the new crucible into the sapphire crystal growth process, thereby controlling the impurities in the sapphire crystal growth, reducing the generation of grain boundaries, stress and bubbles, avoiding the crystal from presenting light green or other colors, ensuring the quality and stability of crystal growth, and improving the quality and consistency of crystal growth.
[0007] The present invention provides a method for controlling impurities in sapphire crystal growth, comprising the following steps:
[0008] S1. Crucible impurity removal: spraying alumina solution on the inner wall of molybdenum crucible, placing the crucible in a crystal growth furnace, sealing the furnace body, and starting heating and sintering and cooling;
[0009] Among them, temperature rise sintering: after vacuuming in the first stage, the vacuum degree is controlled at ≤500Torr, and then the temperature is raised to 400-500℃, and maintained for 0.5-3h. In the second stage, the protective gas is filled and the temperature is continued to rise to 700-750℃, and maintained for 0.5-3h. In the third stage, the temperature is continued to rise to 2055-2065℃, and maintained for 8-12h.
[0010] S2. Crystal growth: The alumina raw material powder is filled into the processed crucible. After the furnace body is sealed, the temperature is raised to melt the raw material. After the raw material is melted, seeding and crystal growth are carried out. After the crystal growth is completed, the crystal is cooled and taken out.
[0011] Among them, in step S1, the crucible needs to be cleaned before impurities are removed. First, pure water is used for ultrasonic cleaning to shake out impurities in the crucible or the slit. Pure water can also effectively avoid the introduction of other impurity elements in the cleaning solution when cleaning the crucible; after drying, the crucible is cleaned with an alcohol solution. This is because the molybdenum crucible may be oxidized, and its oxide is slightly soluble in water. Alcohol is used to clean the dried crucible to remove water-soluble impurities and precipitates generated after drying;
[0012] Preferably, in step S1, the crucible is ultrasonically cleaned for 4-5 hours.
[0013] Preferably, in step S1, the alumina solution is a colorless transparent solution formed by mixing nano alumina powder with a particle size of 5-10 nm and a suspending agent, which are mixed in a mass ratio of 3-6:1, and the suspending agent is a polyacrylic acid water-based solution. After the nano alumina powder is mixed with the suspending agent, it is treated by a hydrothermal method, and the alumina solution has a certain adhesiveness, and is more likely to adhere to the surface of the crucible to form a reaction layer, and react with impurities at high temperature, thereby effectively controlling the impurity content.
[0014] Preferably, in step S1, the temperature of the alumina solution is 40-50°C. Too low a temperature will result in poor fluidity of the raw material, while too high a temperature will cause decomposition of the alumina. This temperature range helps to improve its fluidity during spraying and form a uniform alumina coating; the spraying pressure is set at 0.3-0.5MPa, and the spraying angle is set at 45-60°; the spraying thickness is 1-2mm to ensure that it is uniform, dense, and free of bubbles or shedding.
[0015] Preferably, during the temperature rising sintering process in step S1, after the first stage of vacuuming, the vacuum degree is controlled at ≤400Torr to ensure the good air tightness of the crystal growing furnace, and the temperature is raised to 430-480°C after vacuuming and maintained for 1-2h; in the second stage, the temperature is continued to rise to 710-730°C after the protective gas is filled and maintained for 1-2h; in the third stage, the temperature is continued to rise to 2058-2062°C and maintained for 9-11h, which refers to the temperature close to the liquid surface in the crucible.
[0016] Preferably, in the temperature rising sintering process in step S1, the temperature rising time of the first stage is 6-10 hours, the temperature rising time of the second stage is 3-4 hours, and the temperature rising time of the third stage is 20-25 hours.
[0017] Preferably, in the temperature rising sintering process in step S1, the temperature rising time of the first stage is 7h, 8h or 9h, the temperature rising time of the second stage is 3.2h, 3.4h, 3.6h or 3.8h, and the temperature rising time of the third stage is 21h, 22h, 23h or 24h.
[0018] Preferably, the protective gas is hydrogen.
[0019] In the first stage of the heating and sintering process in step S1, after vacuuming, the vacuum degree in the furnace is relatively high, and there is still a small amount of oxygen in the furnace. As the temperature of the molybdenum crucible continues to rise in this stage, when the temperature is greater than 400°C, a slight and slow oxidation reaction of molybdenum will occur;
[0020] In the second stage of the heating and sintering process in step S1, since aluminum oxide decomposes at high temperature to produce oxygen-poor free atoms, molybdenum reacts with oxygen atoms in a solid state to generate molybdenum trioxide solid, which is distributed on the inner wall of the crucible. As the temperature gradually rises, the molybdenum trioxide in the environment also reacts with aluminum oxide in a solid phase to generate aluminum molybdate, which adheres to the inner wall of the crucible to form a protective layer.
[0021] Since a protective layer is attached to the inner wall of the crucible, the alumina powder raw material is isolated from the inner wall of the molybdenum crucible during the crystal growth process, effectively controlling the precipitation of molybdenum elements in the crucible that affect the quality of crystal growth.
[0022] Aluminum molybdate is odorless and light green, with a density of 3.46-3.49 g / cm 3 , the density of artificial sapphire crystal is 3.4-4.1g / cm 3 The density of aluminum molybdate is close to that of sapphire. If there is no protective layer on the inner wall of the molybdenum crucible, the molybdenum element on the inner wall of the molybdenum crucible will react with the aluminum oxide raw material during the crystal growth process, causing the reaction products to mix into the sapphire crystal, causing the edge of the growing sapphire crystal to appear light green or other colors.
[0023] Preferably, in the third stage of the heating and sintering process in step S1, the temperature is raised to a relatively high temperature for a long time to completely melt the remaining aluminum oxide that has not reacted with the molybdenum trioxide.
[0024] Since the boiling point of molybdenum trioxide is 1155°C, in the third stage of the temperature-raising sintering process in step S1, the unreacted molybdenum trioxide in the crucible will volatilize under the high-temperature environment. Since the protective gas is continuously filled into and discharged from the crucible, the gas circulation will discharge the volatilized molybdenum trioxide gas from the crucible to ensure that the residual molybdenum trioxide is discharged. Therefore, the temperature-raising sintering process in step S1 can effectively remove the free impurity molybdenum element inside the crucible.
[0025] In the cooling process in step S1, the temperature is lowered at a rate of 20-60° C. / h, and the crucible is taken out after cooling to room temperature;
[0026] Preferably, during the cooling process in step S1, the cooling rate above 1200°C is 40-60°C / h, the cooling rate between 800-1200°C is 30-40°C / h, and the cooling rate below 800°C is 20-35°C / h. After the power drops to zero, it is naturally cooled to room temperature.
[0027] In step S2, the purity of the alumina raw material powder used is ≥99.9999%, the average particle size is ≤3μm, and the density is 3.9g / cm 3 .
[0028] In step S2, the temperature in the furnace needs to be heated to 10-20°C above the melting point of alumina to completely melt the alumina raw material to form a melt, and the preferred temperature range is 2060-2065°C.
[0029] Among them, in step S2, after the raw materials are melted and the seed crystal head on the seed crystal rod is uniformly dissolved by 2-5 mm, the seed crystal is sunk until it contacts the surface of the melt to start seeding.
[0030] Among them, in step S2, after the seeding is completed, the sapphire crystal nucleus is formed, the heating power is reduced at a rate of 2-5°C / h, and the cooling rate is controlled to allow the sapphire single crystal to gradually crystallize and grow downward from the top.
[0031] Among them, in step S2, after the crystal growth is completed, the crystal is pulled upward at a rate of 10-12 mm / min to separate the crystal from the solution at the bottom of the crucible, and the temperature is lowered at a rate of 15-20°C / h until it reaches room temperature and then the crystal is taken out.
[0032] The invention provides a crucible for crystal growth, which is a crucible obtained after the crucible is impurity-removed in the above-mentioned sapphire crystal growth impurity control method.
[0033] Among them, the inner wall of the crucible used for crystal growth is covered with an aluminum molybdate protective layer with a layer thickness of 40-100μm.
[0034] The present invention provides an impurity control method for sapphire crystal growth, including two parts: crucible impurity removal and crystal growth. First, the crucible is cleaned, which can not only remove large particles of impurities, but also effectively remove tiny particles and dirt attached to the inner wall of the crucible to ensure the cleanliness of the crucible; then, the molybdenum crucible is sintered at high temperature so that the impurity molybdenum element on the inner wall of the molybdenum crucible can be fully reacted and released, effectively controlling the impurity elements in the crucible. In addition, during the heating process, the molybdenum impurities will react at each heating stage, and finally react with alumina on the inner wall of the crucible to form aluminum molybdate. In the subsequent crystal growth process, this protective layer will isolate the impurity molybdenum element on the inner wall of the crucible from the alumina raw material during crystal growth, prevent direct reaction, and avoid the reaction product from mixing into the sapphire crystal, which is conducive to reducing the generation of grain boundaries, stress and bubbles in the crystal, avoiding crystal discoloration, and improving the quality of sapphire crystal growth. At the same time, the present invention can further enhance the high temperature resistance of the crucible, effectively improve the service life of the crucible, and reduce production costs.
[0035] It has the following beneficial effects:
[0036] 1. Improve the quality of crystal growth: The aluminum molybdate protective layer formed by chemical reaction can reduce the release of impurities from the inner wall of the crucible, provide a purer environment for crystal growth, and help obtain higher quality and more uniform crystals. During crystal growth, trace amounts of molybdenum will affect the electrical properties of the crystal and cause the crystal to discolor. The protective layer can effectively reduce the impact of impurities;
[0037] 2. Improve the service life of the crucible: The aluminum molybdate protective layer attached to the inner wall of the crucible can effectively reduce the loss of the crucible in a high temperature and chemical corrosion environment, thereby extending its service life. During the crystal growth process, high temperature and chemicals will gradually erode the inner wall of the crucible, and the existence of the protective layer can greatly slow down the erosion rate;
[0038] 3. Reduce production costs: By extending the service life of the crucible and reducing the frequency of crucible replacement, the equipment cost in the production process is reduced;
[0039] 4. Enhanced process stability: The protective layer can make the physical and chemical properties of the inner wall of the crucible more stable, reducing process fluctuations caused by crucible changes. In the crystal growth process that requires extremely demanding process conditions, stable crucible performance is essential to ensure product consistency and reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is an electron microscope image of the inner wall of the crucible after the crucible is decontaminated in an embodiment of the present invention. DETAILED DESCRIPTION
[0041] The examples are as follows:
[0042] A method for controlling impurities in sapphire crystal growth, comprising the following steps:
[0043] S1. Crucible impurity removal process is as follows:
[0044] Crucible cleaning: Use a robotic arm to place a new crucible into a container filled with pure water (the new crucible is a molybdenum crucible that has never been used for crystal growth). The container is equipped with an ultrasonic generator. After continuous cleaning for 4 hours, it is placed in a drying room for drying. It is then cleaned with an alcohol solution to remove water-soluble impurities and possible precipitates produced during the drying process. Alcohol has good solubility and volatility and can effectively remove impurities on the surface of the crucible. Finally, it is dried to obtain a crucible with a high inner wall cleanliness, providing a good base for the alumina spraying step.
[0045] Alumina spraying: spraying an alumina solution on the inner wall of a molybdenum crucible. The alumina solution is a mixture of nano alumina powder with a particle size of 5-10nm and a polyacrylic acid water-based suspension in a mass ratio of 4:1. After heating it to 40-50°C, it is loaded into a spray gun, and the spraying pressure is set to 0.3-0.5MPa, and the spraying angle is 45-60°. At this time, the crucible rotates slowly at a speed of 3r / min so that the spray gun can evenly spray the alumina solution on the inner wall of the crucible, and the thickness of the alumina coating is controlled within the range of 1-2mm; the crucible is placed in a crystal growth furnace, and the furnace body is sealed and then the temperature is increased for sintering and the temperature is decreased for cooling, wherein,
[0046] Temperature sintering: In the first stage, the vacuum pump is turned on to evacuate the vacuum, and the vacuum degree in the furnace is maintained below 400Torr, and then the temperature is increased. The heating rate is controlled within 70-100℃ / h, and the temperature is increased for 6-10h until the temperature reaches 400-500℃, and it is maintained at this temperature for 1-2h; in the second stage, hydrogen is filled into the furnace and the temperature is continued to increase. The heating rate is controlled within 30-50℃ / h, and the temperature is increased for 3-4h until the temperature reaches 700-750℃, and it is maintained at this temperature for 1-2h; in the third stage, the temperature is continued to increase for 20-25h, and the heating rate is controlled within 50-70℃ / h, until the equipment output reaches 40-60%, the temperature reaches 2055-2065℃, and it is maintained at this temperature for 10h;
[0047] Cooling: The cooling rate above 1200℃ is 40-60℃ / h, the cooling rate between 800-1200℃ is 30-40℃ / h, and the cooling rate below 800℃ is 20-35℃ / h. The power is reduced to zero and the natural cooling stage is started until the crucible is taken out after it cools to room temperature.
[0048] After the new crucible was treated with impurities, the electron microscope analysis showed that the shallow surface of the inner wall of the crucible had changed in appearance, and a shallow aluminum molybdate film was formed by reaction, such as Figure 1As shown, the immersion depth is 50μm, and the aluminum content in the film material is detected to be 0.17%. This data proves that aluminum oxide reacts with molybdenum crucible to form a shallow aluminum molybdate film, which adheres to the inner wall of the crucible to form a protective layer, inhibiting the release of molybdenum;
[0049] S2. Crystal growth: Alumina raw material powder with a purity of ≥99.9999% and an average particle size of ≤3μm is filled into the treated crucible, the furnace body is sealed and the raw material is melted, seeding and crystal growth are carried out after the raw material is melted, and finally the crystal is removed by cooling.
[0050] Raw material melting: Turn on the vacuum pump to evacuate the furnace, maintain the vacuum degree in the furnace below 400Torr, then increase the temperature at a rate of 50-100℃ / h until the equipment output reaches 40-60%, and heat the furnace to 10-20℃ above the melting point of alumina (2050℃) to completely melt it into a melt;
[0051] Seeding: After the head of a single crystal seed is uniformly dissolved by 2-5 mm, the seed crystal is sunk until it touches the melt surface;
[0052] Crystal growth: After seeding, sapphire nuclei are formed, the heating power is reduced at a rate of 2°C / h, and the cooling rate is controlled to allow the sapphire single crystal to grow gradually from top to bottom;
[0053] Cooling: After the crystal growth is completed, pull the crystal upward to separate the crystal from the solution at the bottom of the crucible, and cool it down at a rate of 15℃-20℃ / h until it reaches room temperature and then take out the crystal.
[0054] Compared with the embodiment, the comparative example did not perform the crucible impurity removal operation, and directly used a new crucible for crystal growth, and the crystal growth parameters were the same as those of the embodiment. The effects of the embodiment and the comparative example are compared as follows:
[0055] (1) Impurity element content test and effect: In the comparative example, the molybdenum content of the first three batches of sapphire crystals after the new crucible crystal growth without impurity removal treatment was relatively high. In the example, the molybdenum content of the first three batches of sapphire crystals after the new crucible crystal growth after impurity removal treatment was obvious. The average removal efficiency of the molybdenum element was calculated to be more than 85%, as shown in Table 1. Removal efficiency = (original content - content after treatment) / original content.
[0056] Table 1 Comparison of molybdenum content in sapphire crystal
[0057]
[0058] (2) Sapphire crystal growth quality test and results: For the comparatively grown sapphire crystal, the average grain boundary density is about 50 / cm 2 The average stress concentration density is about 20 / cm2 The average bubble density is about 30 / cm 2 ; The grain boundary density of the sapphire crystal grown in the embodiment is reduced to an average of 10 / cm 2 Below, the stress concentration density is reduced to an average of 5 / cm 2 Below, the bubble density is reduced to an average of 5 / cm 2 the following.
[0059] (3) Crystal color test and effect: The sapphire crystal grown in the comparative example has a light green edge; the sapphire crystal grown in the example has no light green edge color.
[0060] (4) Crucible service life test and effect: The crucible without impurity removal in the comparative example was used continuously for crystal growth, and the service life of the crucible was about 20 crystal growth cycles. After 20 times, a new crucible needed to be replaced. The crucible with impurity removal in the embodiment was used continuously for crystal growth, and the service life of the crucible reached more than 30 crystal growth cycles.
[0061] In summary, the experimental data of this embodiment fully demonstrates the remarkable effects of the inventive method in controlling impurity elements in the new crucible, improving the growth quality of sapphire crystals and extending the service life of the crucible.
Claims
1. A method for controlling impurities in sapphire crystal growth, characterized in that: The following steps are involved: S1. Crucible impurity removal: spraying an alumina solution on the inner wall of a molybdenum crucible, placing the crucible in a crystal growth furnace, sealing the furnace body, and starting heating and sintering and cooling. The alumina solution is a colorless and transparent solution formed by mixing nano alumina powder with a particle size of 5-10 nm and a suspending agent in a mass ratio of 3-6:
1. The temperature of the alumina solution is controlled to be 40-50°C, the spraying pressure is set at 0.3-0.5MPa, the spraying angle is set at 45-60°, and the spraying thickness is 1-2mm. Among them, temperature rise sintering: after vacuuming in the first stage, the vacuum degree is controlled at ≤500Torr, and then the temperature is raised to 400-500℃, and maintained for 0.5-3h. In the second stage, the protective gas is filled and the temperature is continued to rise to 700-750℃, and maintained for 0.5-3h. In the third stage, the temperature is continued to rise to 2055-2065℃, and maintained for 8-12h. S2. Crystal growth: The alumina raw material powder is filled into the processed crucible. After the furnace body is sealed, the temperature is raised to melt the raw material. After the raw material is melted, seeding and crystal growth are carried out. After the crystal growth is completed, the crystal is cooled and taken out.
2. The control method according to claim 1, characterized in that: In the step S1, the crucible needs to be cleaned before impurities are removed. First, it is cleaned ultrasonically with pure water, and then the crucible is cleaned with an alcohol solution after drying.
3. The control method according to claim 1, characterized in that: In the step S1, the suspending agent is a polyacrylic acid water-based solution.
4. The control method according to claim 1, characterized in that: During the temperature rising sintering process in step S1, after vacuuming in the first stage, the vacuum degree is controlled at ≤400Torr, and the temperature is raised to 430-480°C after vacuuming and maintained for 1-2 hours; in the second stage, the temperature is continued to rise to 710-730°C after the protective gas is filled and maintained for 1-2 hours; in the third stage, the temperature is continued to rise to 2058-2062°C and maintained for 9-11 hours, where the temperature refers to the temperature close to the liquid surface in the crucible.
5. The control method according to claim 4, characterized in that: In the temperature rising sintering process in step S1, the temperature rising time of the first stage is 6-10 hours, the temperature rising time of the second stage is 3-4 hours, the protective gas is hydrogen, and the temperature rising time of the third stage is 20-25 hours.
6. The control method according to claim 1, characterized in that: During the cooling process in step S1, the temperature is lowered at a rate of 20-60° C. / h, and the crucible is taken out after cooling to room temperature.
7. The control method according to claim 6, characterized in that: During the cooling process in step S1, the cooling rate is 40-60°C / h above 1200°C, 30-40°C / h between 800-1200°C, and 20-35°C / h below 800°C. After the power drops to zero, the system cools naturally to room temperature.
8. The control method according to claim 1, characterized in that: In the step S2, the temperature in the furnace needs to be heated to 10-20°C above the melting point of alumina, so that the alumina raw material is completely melted to form a melt; after the raw material is melted, after the seed crystal head on the seed crystal rod is evenly dissolved by 2-5mm, the seed crystal is sunk until it contacts the surface of the melt, and seeding begins; after the seeding is completed, a sapphire crystal nucleus is formed, and the heating power is reduced at a rate of 2-5°C / h, and the cooling rate is controlled to allow the sapphire single crystal to gradually crystallize and grow downward from the top; after the crystal growth is completed, the crystal is pulled upward at a rate of 10-12mm / min to separate the crystal from the solution at the bottom of the crucible, and the temperature is reduced at a rate of 15-20°C / h until it reaches room temperature and then the crystal is taken out.
9. A crucible for crystal growth, characterized in that: The crucible is a crucible obtained by removing impurities from the crucible using any one of the control methods described in claims 1-7.
Citation Information
Patent Citations
Polycrystalline silicon ingot and preparation method thereof, polycrystalline silicon wafer and crucible for polycrystalline silicon ingot
CN103361722B
Aluminum molybdate-based microwave dielectric composite ceramic and preparation method thereof
CN108727023A
Aluminum molybdate-based microwave dielectric composite ceramic sintered at extremely low temperature and preparation method thereof
CN110818413A
Crucible for graphite thermal field crystal growth furnace
CN220116725U
Preparation method of high-purity sintered alumina for monocrystal sapphire growth
CN102603273A